The Effect of Earning Per Share and Price Earning Ratio on Stock Price with Dividend Policy as an Intervening Variable - Frida Yuniar Prastika; Muhammad Yusuf (PERFECT EDUCATION FAIRY, 2023)
This study aims to determine the effect of earnings per share and price earning ratio on stock prices with dividend policy as an intervening variable in food & beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research sample was taken with purposive sampling technique which obtained 11 companies and processed with Eviews10 software. The results of this study indicate that (1) EPS has no effect on DPR, (2) PER has a significant positive effect on DPR, (3) EPS has no effect on Stock Price, (4) PER has no effect on Stock Price, (5) DPR has a significant positive effect on Stock Price, (6) EPS and PER have a significant positive effect on DPR, (7) EPS, PER, and DPR have a significant positive effect on Stock Price, (8) EPS has no effect on Stock Price through DPR, (9) PER has a significant positive effect on Stock Price through DPR.